THE DEATH PENALTY IN INDONESIA FROM A HUMAN RIGHTS PERSPECTIVE - Hendro Siburian (Fox Justi : Jurnal Ilmu Hukum, 2022)
The imposition of the death penalty is closely related to the most basic rights for humans, which is a serious crime in the sense that the perpetrator will lose his life which is an invaluable right to life. Law Number 39 of 1999 concerning Human Rights which is an acknowledgment of Human Rights in Indonesia. Giving limits on human rights as a set of rights that are inherent in the nature and existence of humans as creatures of God Almighty and are His gifts that must be respected, upheld and protected by the State, law, government and everyone for the sake of honor and protection of human dignity.